Accelerating 6TiSCH Network Formation - Tanaka, Yasuyuki; Minet, Pascale; Watteyne, Thomas; Teraoka, Fumio (International Conference on Distributed Computing in Sensor Systems and workshops (Online), 2021)
Wireless sensor networking is a key enabler of Industrial IoT. IETF (Internet Engineering Task Force) has standardized a protocol suite called 6TiSCH (IPv6 over the TSCH mode of IEEE802.15.4e). 6TiSCH builds an IPv6 multi-hop wireless network with the IEEE802.15.4 radio, which achieves low energy consumption and high reliability. Although network formation time is one of key performance indicators of wireless sensor networks, it has not been studied well with 6TiSCH standard protocols such as MSF (6TiSCH Minimal Scheduling Function) and CoJP (Constrained Join Protocol). In this paper, we propose a scheduling function called SF-Fastboot which shortens network formation time of 6TiSCH. We evaluate SF-Fastboot by simulation comparing with MSF, the state-of-the-art scheduling function. The simulation shows SF-Fastboot reduces network formation time by 41 % - 80 %.